Compressive behavior of double-tube concrete columns with an outer square FRP tube and an inner circular high-strength steel tube. (30th September 2018) - Zeng, Jun-Jie; Lv, Jun-Fan; Lin, Guan; Guo, Yong-Chang; Li, Li-Juan
Highlights: Hybrid DTCCs with an HSS tube possess excellent load-carrying capacity and axial deformation capacity. Local buckling of the HSS tube in a DTCC can be effectively restrained. Interaction between the HSS tube and the FRP-confined concrete leads to some benefits. Inner HSS tube not only resists axial load, but also provides further confinement to the concrete. Abstract: Double-tube concrete columns (DTCCs) are a novel form of hybrid columns which consist of an outer fiber-reinforced polymer (FRP) tube, an inner circular high-strength steel (HSS) tube and the concrete filled in the entire section. In a DTCC, the inner HSS tube not only effectively diminishes the non-uniformity of stress distribution of concrete in a concrete-filled square FRP tube but also enhances the confinement to the core concrete, with its buckling being effectively restrained by the surrounding concrete and the outer FRP tube. This paper presents the results of an experimental study on the axial compressive behavior of DTCCs with an outer square FRP tube. Eight square DTCC specimens were tested under axial compression. The examined column parameters included FRP tube thickness, FRP tube width, and FRP type. The experimental results show that, in square DTCCs, the concrete is well confined by both the FRP tube and the HSS tube, and the buckling of HSS tube is effectively restrained so that its high material strength can be effectively utilized, leading to an excellent column performance. The experimental results also demonstrate that square DTCCs possess considerable post peak strength, indicating excellent ductility and promising application potential of this new form of hybrid column members in earthquake prone zones.